RANCANG BANGUN ALAT PEMANTAU BERAT MENGGUNAKAN ANDROID BERBASIS MIKROKONTROLER - Ahmad Nurfauzi; Agil Candra Ramadhan; M.Ridwan Arif Cahyono (LPPM Politeknik Jambi, 2022)
Digital scales are measuring instruments to measure the mass weight of objects or substances with a digital display. In its use, scales are used in various fields, from trade, industry to service companies. In this case, digital scales have many advantages, including: the mass of the scale itself is lighter than manual scales, the results of measuring the measured load are more accurate, suitable for measuring small objects, in terms of design digital scales seem more modern and in terms of maintenance required it is very easy to do. Measuring instruments are designed and made by prioritizing the ability of measuring instruments such as accuracy, accuracy, and reading ability. There are two category systems in scales, namely Analog Scales and Digital Scales. Load cell is the core component contained in the Digital Scale which functions as a pressure sensor that will convert the analog signal generated by the Load Cell to the amount of electricity. The reading of the load cell data will be processed by Esp 8266 through the HX711 system to convert the amount of potential that occurs in the load cell into digital data. This method uses the measurement principle carried out by Loadcell using the pressure principle that utilizes the Strain Gauge as a sensor. This is evidenced by the results of testing the condition of the tool in good condition and in accordance with the accuracy when the object is weighed to get a result of 99%.